Legal Consistency of Health Personnel in Making Medical Records - Ambar Dwi Erawati; Seyed Mohammad Asadinejad; Seyedeh Maryam Asadinejad (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: Medical record is a record or document containing patient identity, examination, treatment, action and other services that must be made by health workers, but not 100% complete medical records. Currently, when talking about medical records, doctors always think, while in the law on health workers, medical records must be made by health workersPurpose/Objective Study: to find out the legal certainty of health workers in making medical recordsDesign/Methodology/Approach: This research is normative with deductive research analysis.Findings: the results of patient records carried out by the medical profession are called medical records, patient records carried out by nurses are called nursing care documentation and patient records carried out by midwives are called midwifery care documentation. Doctors who do not make medical records can get criminal sanctions, while nurses and midwives if they do not do documentation of care will get administrative sanctions.Paper Type: Research Article